Mortality and medicine: forms of silence and of speech. Issue 2 (8th December 2003) - Rowe, M
Abstract : Silence can be harmful to patients, their loved ones, and doctors within the contexts of illness and bereavement. I draw from my experience with my son's illness and death to discuss five forms of silence—the silence around the experience of critical illness; the silence between life and death; the silence of doctors; the silence of the dead, and the silence of the ill—and of speech that may emerge in response to these silences.